Little Eve - Ward, Catriona (Nightfire, 2022)
"Winner of the Shirley Jackson Award for best novel and the August Derleth Prize for best horror novel, Catriona Ward's Little Eve is a heart-pounding literary gothic with a devastating twist. Eve and Dinah are everything to one another, together day and night. They are raised among the Children, a clan ruled by a mysterious figure they call Uncle. All they know is the gray Isle of Altnaharra, which sits alone in the black sea off the wildest coast of Scotland. Eve loves the free, savage life of the Isle and longs to inherit Uncle's power. But Dinah longs for something more, something different. With the dawn of the first World War, the solitude of Altnaharra is broken, and soon after, Eve's faith starts to fracture. In the depths of winter, as the old year dies, the nearby townsfolk awaken to discover a massacre on the Isle. Eve and Dinah's accounts of that night contradict and intertwine. As past and present converge, only one woman can be telling the truth. Who is guilty, who innocent? And who can be trusted?"--